Wheat Cost-Return Budget in North Central Kansas - Warmann, Gerald W.; Dhuyvetter, Kevin C. (My University, 1996)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_1996_10
Keywords: MF2158; Crops; Economics; MF